Human Salmonella enteritidis illness outbreak associated with exposure to live mice in British Columbia, Canada, 2018–2019. (1st June 2022) - Plotogea, Amalia; Taylor, Marsha; Parayno, Alicia; Sillje, Mona; Stone, Jason; Byrnes, Rakel; Bitzikos, Olga; Redford, Tony; Waters, Shannon; Fraser, Erin; Hoang, Linda; Zabek, Erin; et al.
Abstract: In February 2019, five individuals with Salmonella Enteritidis infections matching by whole genome sequencing (WGS) were identified in the province of British Columbia (BC), Canada. Individuals with available exposure information all reported unique exposure to reptiles or rodents, prompting an outbreak investigation. We describe how WGS, case interviews, traceback and environmental testing were used to link this outbreak to one supplier of live mice primarily used as feeder rodents for pet snakes. Our investigation suggested that SE infection in the live mice occurred from contact with surfaces at the facility which were contaminated with the bacteria, either by a new stock of mice or by culled chicks routinely brought in and processed at the facility. Timely control measures for biosecurity and hygiene implemented at the supplier contributed to reducing the ongoing risk of illness in humans. This investigation not only contributes to the weight of evidence on the risk that pet or feeder rodents pose, but also highlights how ongoing infections in animal species can result in the spread of Salmonella to humans.